Outcomes of Continuous Ambulatory Peritoneal Dialysis in Treatment of End Stage Renal Disease in Patients Registered at Middle Euphrates Center for Peritoneal Dialysis - Sharba , Yasir Fathi Faleeh; Almatwari, Majid Abdulhameed Muslim; Hussein, Zainab Naser; Joodi, Ameer Najeh (Academic Journal of Clinicians, 2024)
End stage renal disease is a significant health problem worldwide, the ideal treatment option is and earlier kidney transplant but it is neither always possible nor available. Peritoneal dialysis, represents an ideal alternative to kidney transplant Different modalities of peritoneal dialysis (PD) are available. The choice of technique affected by several factors and each option must be tailored to meet patient’s needs and clinical status of the patients. Continuous Ambulatory Peritoneal Dialysis (CAPD) known as a “do it yourself” option, has appeared as a good option and alternative to hospital based or home hemodialysis with some benefits to the patients, their families and health system. In Iraq, CAPD is not widely used across the country and majority of patients still performed hospital based dialysis in many centers across the country. We conducted the present study aiming to assess the outcomes of CAPD in Patients with End Stage Renal Disease Registered in the Middle Euphrates for Peritoneal Dialysis Center in Najaf City. We included 93 adult Iraqi patients of both genders who were registered during the period 2017 – Mid-2024 included. Study findings revealed that Continuous Ambulatory Peritoneal Dialysis (CAPD) is an effective option of renal replacement therapy with important benefits to the patients and can improve their health-related quality of life with little adverse outcomes that were less frequent when compared to other modalities in other studies.